THE EFFECT OF OCCUPATIONAL SAFETY AND HEALTH AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE IN THE ENVIRONMENTAL SERVICES OF YOGYAKARTA CITY - M Hibbul Watoni (International Journal of Economics, Business and Accounting Research (IJEBAR), 2019)
This study aims to investigate the effect of occupational safety and health and work discipline on employee performance in the Environmental Services of Yogyakarta City either partially or simultaneously. The population of this study was 220 employees of the Sanitation Division in the Environmental Services of Yogyakarta City. The current study involved 135 samples who were selected using a random sampling technique. It used primary data and they were collected through distributing a questionnaire. The validity and reliability of the questionnaire have been tested prior to the administration. Then, the data were analyzed by multiple linear regression analysis, t-test, f-test, and determination test using SPSS 20. The result showed that partial testing of occupational safety and health (X1) and work discipline (X2) variables had a significant effect on employee performance (Y) in the Environmental Services of Yogyakarta City. Whereas simultaneous testing of Occupational safety and health (X1) and work discipline (X2) variables significantly affected the employee performance (Y) in the Environmental Services of Yogyakarta City.